EMPOWERING MATERNAL WELLNESS: THE VITAL ROLE OF NURSING ADVOCACY IN MATERNAL MENTAL HEALTH - Priyanka Rajak, Jossy Augustine, Santhosh Kumar , Amrita Singh, Arun James, Elmy Sara Noble, Kitty P Wilson, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
Maternal mental health is a critical component of holistic healthcare during the perinatal period. This article sheds light on the pivotal role that nurses play in advocating for maternal mental health, emphasizing the importance of awareness, education, and policy reform. By exploring the unique challenges faced by pregnant and postpartum individuals, this article underscores the need for comprehensive care and support within the nursing profession.